Spatial Autocorrelation, Source Water and the Distribution of Total and Viable Microbial Abundances within a Crystalline Formation to a Depth of 800 m - Beaton, E. D.; Stuart, Marilyne; Stroes-Gascoyne, Sim; King-Sharp, Karen J.; Gurban, Ioana; Festarini, Amy; Chen, Hui Q. (Frontiers in Microbiology, 2017)
Proposed radioactive waste repositories require long residence times within deep geological settings for which we have little knowledge of local or regional subsurface dynamics that could affect the transport of hazardous species over the period of radioactive decay. Given the role of microbial processes on element speciation and transport, knowledge and understanding of local microbial ecology within geological formations being considered as host formations can aid predictions for long term safety. In this relatively unexplored environment, sampling opportunities are few and opportunistic. We combined the data collected for geochemistry and microbial abundances from multiple sampling opportunities from within a proposed host formation and performed multivariate mixing and mass balance (M3) modeling, spatial analysis and generalized linear modeling to address whether recharge can explain how subsurface communities assemble within fracture water obtained from multiple saturated fractures accessed by boreholes drilled into the crystalline formation underlying the Chalk River Laboratories site (Deep River, ON, Canada). We found that three possible source waters, each of meteoric origin, explained 97% of the samples, these are: modern recharge, recharge from the period of the Laurentide ice sheet retreat (ca. ∼12000 years before present) and a putative saline source assigned as Champlain Sea (also ca. 12000 years before present). The distributed microbial abundances and geochemistry provide a conceptual model of two distinct regions within the subsurface associated with bicarbonate – used as a proxy for modern recharge – and manganese; these regions occur at depths relevant to a proposed repository within the formation. At the scale of sampling, the associated spatial autocorrelation means that abundances linked with geochemistry were not unambiguously discerned, although fine scale Moran’s eigenvector map (MEM) coefficients were correlated with the abundance data and suggest the action of localized processes possibly associated with the manganese and sulfate content of the fracture water.